INFLUENCE OF LOCAL GOVERNMENT POLICIES ON YOUTH-LED TECH STARTUPS IN ENUGU STATE (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2026)
Youth tech startups are such an important component of Nigeria economic diversification especially in the parts of Nigeria where the population has been faced with unemployment and little formal employment. The article examines the role of local governmental policies in the development, sustainability and obstacles on such start-ups. The study analyzed secondary data on government reports, academic literature, and industry reviews of 2010-2025, and found out that policies like the Enugu Startup Bill, forming of Enugu State Tech Hub (ESTHUB), and education of youth in tech activities have hugely positively impacted the formation of startups and over 100 active youth-led tech businesses emerged since 2020. Nevertheless, there remain lapses in terms of funding access, regulatory transparency and infrastructural assistance in promoting scalability. The comparison is based on an ideational framework, informed by an institutional theory, to assess the effectiveness of policies, with the emphasis on the way the targeted interventions may help to increase the rate of innovation and employment. The results highlight the necessity to simplify incentives and collaborations with the state to enhance the effectiveness of the policies. This publication can contribute to the discussion about subnational governance in the African tech ecosystems and can be used to provide some recommendations to the policymakers about various ways to create inclusive entrepreneurial conditions in the economy.